PERBANDINGAN HASIL BELAJAR FISIKA SISWA YANG DIAJARKAN MELALUI MODEL PEMBELAJARAN QUANTUM LEARNING DAN QUANTUM TEACHING DI SMPN 8 BANDA ACEH - Sarah Nadia (Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2016)
Learning results are indicators target achievement planned. Speaking about the results of the study, physics is one of the subjects that can shares categorize as subjects that have the results of the study is relatively low. Based on the results of previous research that shows that the model of Quantum Learning and Quantum Teaching can improve the results of the study of physics students. This research raise issues about how the results of learning physics students who taught through the model of Quantum Learning compared with that taught through the model of Quantum Teaching. The approach used in this research is the approach kuantatif. The population of this research on all the students of class VII SMP 8 Banda Aceh namely 5 class. The population is assigned a sample of some 25 class experiment I and 23 class experiment II. The sample selection is done by purposive sampling. The method used is the method of the experiment. Data Collection in this research consists of data pre-test and post-test. Data processing techniques using the test statistics t. After the collected data and the data is processed, though the results of the analysis of the data showed that the class experiment I and experiment II has the spread of the value of the test berdistribusi normal, and have homogeneous varians. So research can continue. The end result obtained t-count ttable  namely 3,431 2.02. Then the hypothesis of zero (